Acceptance of IoT learning among university students at Pakistan - Shaikh, Humaiz; Maher, Zulfikar Ahmed; Raza, Ali; Koondhar, Muhammad Yaqoob; Hussain, Saajid; Shah, Asadullah (2021)
The Internet of Things abbreviated as an IoT is considered the most recent innovative and fastest-developing field that is to be applied in all aspects of life, in particular higher education. It has sparked interest as well as challenges among academics; the current research will concentrate on acceptance and adoption of IoT in the higher educational institutions of Pakistan. IoT supports educators in environment of learning and can have an impact on how we interact, connect, and work. In this study, we will look at two different aspects. The first one is how to teach students, and secondly how IoT can be used in educational institutions to enhance learning. This study looks at the factors that affect acceptance of IoT and use in an academic setting in Pakistan's higher education institutions. The current research establishes foundation for a comprehensive framework based on trusted technology and social psychology models, such as the Use of Technology 2 and Unified Theory of Acceptance (UTAUT2). The method proposed in this study is network analysis method to observe users' actions in relation to several IoT applications in higher education. An in-depth analysis and consideration of key deliverables which have a major impact on the Internet of Things (IoT) adoption in Pakistani educational institutions of higher level, revealed that only a few applications are heavily used in comparison to all other applications. This research lays the groundwork for developed countries to grow adoption and IoT technologies use in higher education, which will support both students and faculty.